The Influence of Organizational Culture in Increasing Staff Work Effectiveness at LPK Horison, Bekasi City - Siti Humayroh; Agus Cholik; Silvia Oktaviani; Ratna Dewi; Anton Sujarwo (International Publisher, 2024)
This study aims to analyze the influence of organizational culture on the effectiveness of staff work at the Horison Job Training Institute (LPK) in Bekasi City. Using a quantitative approach and survey method, this study involved 50 employees as respondents selected using a saturated sampling technique. Data were collected through validated questionnaires and analyzed using simple linear regression analysis. The results showed that organizational culture has a positive and significant influence on staff work effectiveness with a coefficient of determination (R²) value of 0.724, indicating that 72.4 % of the variation in work effectiveness can be explained by organizational culture. The most influential dimensions of organizational culture are innovation and risk taking, with a contribution of 31.2 % . This study provides practical implications for LPK Horison management in developing strategies to strengthen organizational culture to improve staff work effectiveness.